Primary sclerosing cholangitis and autoimmune hepatitis overlap syndrome associated with inflammatory bowel disease: A case report and systematic review - Ballotin, Vinícius Remus (World J Clin Cases, 2020)
BACKGROUND: A previously healthy 22-year-old woman presented with abdominal pain and jaundice. She had a reagent antinuclear factor (1:640, with a homogeneous nuclear pattern) and hypergammaglobulinemia (2.16 g/dL). Anti-smooth muscle, anti-mitochondrial and anti-liver-kidney microsomal antibody type 1 antibodies were negative. Magnetic resonance cholangiography showed a cirrhotic liver with multiple focal areas of strictures of the intrahepatic bile ducts, with associated dilations. Liver biopsy demonstrated periportal necroinflammatory activity, plasmocyte infiltration and advanced fibrosis. Colonoscopy showed ulcerative pancolitis and mild activity (Mayo score 1), with a spared rectum. Treatment with corticosteroids, azathioprine, ursodeoxycholic acid and mesalamine was initiated, with improvement in laboratory tests. The patient was referred for a liver transplantation evaluation. AIM: To report the case of a female patient with autoimmune hepatitis and primary sclerosing cholangitis (PSC) overlap syndrome associated with ulcerative colitis and to systematically review the available cases of autoimmune hepatitis and PSC overlap syndrome. METHODS: In accordance with preferred reporting items for systematic reviews and meta-analysis protocols guidelines, retrieval of studies was based on medical subject headings and health sciences descriptors, which were combined using Boolean operators. Searches were run on the electronic databases Scopus, Web of Science, MEDLINE (PubMed), Biblioteca Regional de Medicina, Latin American and Caribbean Health Sciences Literature, Cochrane Library for Systematic Reviews and Opengray.eu. Languages were restricted to English, Spanish and Portuguese. There was no date of publication restrictions. The reference lists of the studies retrieved were searched manually. RESULTS: The search strategy retrieved 3349 references. In the final analysis, 44 references were included, with a total of 109 cases reported. The most common clinical finding was jaundice and 43.5% of cases were associated with inflammatory bowel disease. Of these, 27.6% were cases of Crohn’s disease, 68% of ulcerative colitis, and 6.4% of indeterminate colitis. Most patients were treated with steroids. All-cause mortality was 3.7%. CONCLUSION: PSC and autoimmune hepatitis overlap syndrome is generally associated with inflammatory bowel disease and has low mortality and good response to treatment.